2005
DOI: 10.1037/h0088903
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural trends and toys in play therapy.

Abstract: Because culture plays an increasingly important role in play therapy, the purpose of this article is to review existing literature on multicultural issues in play therapy and to discuss current trends and toys in play therapy reported from a group of play therapists. A group of play therapists (N = 505) registered with the Association for Play Therapy were asked to respond to two open-ended questions: What trends, if any, do you see in play therapy with your culturally diverse clients? What items do you includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…With regard to the play therapy profession, although participants reported that 36% of their clients were African American or Latino, only 3% of the respondents were African American and none of the respondents identified themselves as Latino. Given that play therapists are experiencing an increase in the number of racial and ethnic minority children and parents they serve (Chang et al, 2005), it seems imperative that the play therapy profession incorporate strategies to broaden the demographic scope of APT membership. This notion is also echoed by Abrams et al (2006), who asserted that the population of practicing play therapists ought to be diversified to meet the needs of clients with varied backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the play therapy profession, although participants reported that 36% of their clients were African American or Latino, only 3% of the respondents were African American and none of the respondents identified themselves as Latino. Given that play therapists are experiencing an increase in the number of racial and ethnic minority children and parents they serve (Chang et al, 2005), it seems imperative that the play therapy profession incorporate strategies to broaden the demographic scope of APT membership. This notion is also echoed by Abrams et al (2006), who asserted that the population of practicing play therapists ought to be diversified to meet the needs of clients with varied backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Although researchers have emphasized the need for culturally responsive services (e.g., Ceballos & Bratton, 2010; Garza & Bratton, 2005; Perez et al, 2007; Sheely‐Moore & Bratton, 2010) and multicultural education and supervision (Chang et al, 2005; VanderGast et al, 2010) in the play therapy field, SJA has barely been addressed. A review of the play therapy literature revealed two articles (Baggerly, 2006; O'Connor, 2005) that mention the importance of understanding and addressing the impact of social factors on client well‐being.…”
Section: Social Justice Advocacy and Play Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ST has been documented across time and cultures, and has developed out of personal phenomenological hermeneutic research (De Domenico, 1988;Graham, Scholl, Smith-Adcock, & Wittmann, 2014). Originally developed out of Lowenfeld's (1979) world technique and modified by Kalff (2004), ST has been purported to promote healing and growth, effectively respond to trauma, increase self-esteem, facilitate the counseling process and counteract resistance, and attend to culturally specific issues, such as gender and race (Chang, Ritter, & Hays, 2005;Paone et al, 2015). Stark and Frels (2014) suggested that ST also offers opportunities as a collaborative assessment for counselor development, especially with counselors-in-training.…”
Section: Sand Tray: a Creative Approachmentioning
confidence: 99%
“…Stark and Frels (2014) suggested that ST also offers opportunities as a collaborative assessment for counselor development, especially with counselors-in-training. As an expressive arts supervision activity, ST provides a shared symbolic language for supervisee and supervisor, and can assist in exploring case conceptualization and counseling dynamics (Chang et al, 2005;Stark, Garza, Bruhn, & Ane, 2015), as well as increasing supervisee self-awareness and expression (Carnes-Holt, Meany-Walen, & Felton, 2014;Garrett, 2015a;McCurdy & Owen, 2008).…”
Section: Sand Tray: a Creative Approachmentioning
confidence: 99%